White Racial Awareness: Complexities and Contexts of White Educator Identities. (February 2022) - Deutschman, Megan C.
This study utilizes life history methodology to understand how White teachers develop racial awareness while also exploring how the education profession acts as an inflection point for racialized understandings of the world. Furthermore, as the educators in this study grew in their racial awareness, there was a rise in conflicting and ambivalent feelings as they attempted to teach in ways that aligned with their newly developed awareness. These feelings surfaced as the educators grappled with issues of race, Whiteness, and systemic inequality in both their profession and in their personal lives. Using a framework of Critical Whiteness Studies, this study provides a nuanced and contextual discussion of White identity development. Ultimately, findings show that educators begin to understand race through proximity, exposure, and repeated interaction with students of Color. This holds major implications not only for educators and teacher education programs but also for students of Color.